Ameliorative effect of curcuminoids in liver fibrosis rat model via regulating GIPC1 gene and modulating MMP-8/TIMP-3 balance mediated by miR-483-5p - Rana Mostafa Adel; Sara Mostafa Kamal; Eman Adel Sherif; Sara Hatem El-shafiey (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Liver fibrosis is a worldwide disease that develops from activation and propagation of hepatic stellate cells, and subsequent extracellular matrix accumulation. Liver fibrosis is associated with multiple pathways, however, the dysregulation of GIPC1 gene (GIPC PDZ domain containing family member 1) and disruption in the balance of MMPs (matrix metalloproteinases) and TIMPs (tissue inhibitor of metalloproteinases) remain as key factors in this disease. Curcuminoids, especially curcumin (CURC), are medicinal extracts that proved their antioxidative, anti-inflammatory, antifibrotic actions, and showed wide epigenetic regulatory effects. We aimed to explore CURC’s effect on declining the inflammatory cytokines TNF-α (tumor necrosis factor-alpha), IL-6 (interleukin-6), TGF-β1 (transforming growth factor beta1), regulating GIPC1 expression, and adjusting MMP-8/TIMP-3 balance mediated by miRNA-483-5p (microRNA-483-5p) in TAA (thioacetamide)-induced liver fibrotic albino Wistar rat model. Results The attained results revealed significant regressions in livers’ relative weights, serum ALT (alanine aminotransferase), AST (aspartate aminotransferase), ALP (alkaline phosphatase) and LDH (lactate dehydrogenase), plasma PDGF (platelet-derived growth factor), liver TOC (total oxidative capacity), TNF-α, IL-6, TGF-β1, and downregulation in GIPC1 gene expression, besides, significant elevation in liver TAC (total antioxidant capacity) in CURC-treated rats. Surprisingly, significant upregulation in miRNA-483 expression was obtained in CURC-treated rats which consequentially enhanced MMP-8/TIMP-3 balance in the form of an elevation in MMP-8/reduction in TIMP-3 levels, along with confirming this novel pathway through conducting bioinformatics analysis. All these enhancements were mirrored in Annexin V/PI (Annexin V Propidium Iodide) assay as massive improvements in % of apoptotic and necrotic cells, plus, in H&E (hematoxylin and eosin) and Masson’s trichrome histopathological examinations that showed near to normal liver architecture with no collagen bands deposition. Conclusions This study concludes that CURC can modulate the novel miRNA-483-5p/MMP-8/TIMP-3 pathway and regulate GIPC1 expression, thus providing new perception of CURC as an effective therapeutic agent capable of lowering inflammation and remodeling liver damage. Graphical Abstract